ANALISIS KEBIJAKAN LUAR NEGERI RUSIA DALAM KLAIM WILAYAH ARKTIK TAHUN 2001-2009 - Anggreani, Nova Lita (2020)
Arctic is one of the oceans in the world which has many reserves of natural resources. Since the Arctic sea ice begins to melt, several countries around Arctic tried to claim the ownership of territories beyond the predetermined continental boundaries. Russia is one of the countries that made the claim, and in 2001, Russia had focused on arranging several policies for the Arctic. An explanatory research was implemented to examine the reasons why Russia made territorial claims in the Arctic. According to William D. Coplin, there are three considerations which influence decision makers in arranging the foreign policy, such as the international context, domestic political conditions, and economic and military conditions of a country. The results of the study revealed that Russia's desire to become the strongest country in the world was the main reason that influenced Russia to arrange a foreign policy, and influenced by Gazprom, the company which becomes the interest influencer. Thus, Russia will increase the exports of its natural resources in order to enhance the dependence on other countries, and also increase the military capacity in the Arctic to protect it from any attacks of other countries.